2009
DOI: 10.3766/jaaa.20.4.4
|View full text |Cite
|
Sign up to set email alerts
|

The Time Course of the Amplitude and Latency in the Auditory Late Response Evoked by Repeated Tone Bursts

Abstract: The reduction of latency in the time course of the ALR might be related to the fact that neurons with shorter latencies had faster recovery speed from adaptation and/or refractoriness than those with longer latencies. This finding is meaningful in the context of future research to restore normal adaptation in abnormal hearing populations such as cochlear implant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 57 publications
5
20
0
Order By: Relevance
“…The finding of less prominent adaptive pattern in CI users compared to NH listeners in the current study is consistent with that reported in Zhang et al [56]. One explanation for the reduced amount of adaptation in CI users is that neural degeneration may have altered the adaptation/refractory features of neural responses [58]. This explanation is supported by a significant correlation between AI LAEP and the age at implantation, which is a factor affecting the degree of neural degeneration.…”
Section: Discussionsupporting
confidence: 92%
“…The finding of less prominent adaptive pattern in CI users compared to NH listeners in the current study is consistent with that reported in Zhang et al [56]. One explanation for the reduced amount of adaptation in CI users is that neural degeneration may have altered the adaptation/refractory features of neural responses [58]. This explanation is supported by a significant correlation between AI LAEP and the age at implantation, which is a factor affecting the degree of neural degeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Second, to assess the amplitude attenuation profile in response to increasing RAS frequencies, repeated measures ANOVAs were performed for peak-to-peak amplitudes of the P1/ N1-complex (Papanicolaou et al, 1984;Lim et al, 2005). This peak-to-peak assessment is not influenced by baseline resetting effects due to preceding AEPs and may be considered a more stable measure than absolute amplitude of individual peak components (Zhang et al, 2009). ANOVAs were performed in PASW Statistics (PASW Statistics for Mac, version 18.0, SPSS Inc., Chicago, IL, USA) in two ways: (1) with the within-subjects factors RAS (from 1 Hz to 6 Hz) and the between-subjects factor Group (controls vs. experimental conditions of the patient cohort) for differences between patients and controls; and (2) with the within-subjects factors RAS (from 1 Hz to 6 Hz) and Treatment (DOPA-ON, DOPA-OFF, ON-DBS, OFF-DBS).…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of such a phase reset or if stimuli occur in a non-ideal phase, behavioral responses are suppressed or slowed down. (c) When the timing of a sound is correctly anticipated (right panel), a decrease in evoked auditory responses (N1) is observed [22,23]. This schematic compares the amplitude of an event-related response (N1, averaged across 10 trials) to unexpected (left panel) and expected (right panel) auditory stimuli.…”
Section: Predictive Timing and Delta-theta Oscillationsmentioning
confidence: 98%
“…The predictive alignment of delta-theta oscillations in an ideal excitability phase speeds up stimulus detection (Figure 1b) [20,21]. Furthermore, when stimuli are implicitly expected based on their temporal regularity, early sensory responses are reduced (Figure 1c) [22,23]. The magnitude of neural responses, however, depends on whether temporal predictions are tested in the presence or absence of explicit attention to the nature or location of those events (Box 1 and [24][25][26][27]).…”
Section: Predictive Timing and Delta-theta Oscillationsmentioning
confidence: 99%